Adverse Selection in the Marriage Market: HIV Testing and Marriage in Rural Malawi - Manuela Angelucci; Daniel Bennett (Institute of Labor Economics (IZA), 2020)
Asymmetric information in the marriage market may cause adverse selection and delay marriage if partner quality is revealed over time. Sexual safety is an important but hidden partner attribute, especially in areas where HIV is endemic. A model of positive assortative matching with both observable (attractiveness) and hidden (sexual safety) attributes predicts that removing the asymmetric information about sexual safety accelerates marriage and pregnancy for safe respondents, and more so if they are also attractive. Frequent HIV testing may enable safe people to signal and screen. Consistent with these predictions, we show that a high-frequency, "opt-out" HIV testing intervention changed beliefs about partner's safety and accelerated marriage and pregnancy, increasing the probabilities of marriage and pregnancy by 26 and 27 percent for baseline-unmarried women over 28 months. Estimates are larger for safe and attractive respondents. Conversely, a single-test intervention lacks these effects, consistent with other HIV testing evaluations in the literature. Our findings suggest that an endogenous response to HIV risk may explain why the HIV/AIDS epidemic has coincided with systematic marriage and pregnancy delays.
Keywords: J12; J13; I15; I18; 330; adverse selection; marriage; HIV